IMPLEMENTASI PENDIDIKAN LIFE SKILL BERBASIS AL-QURAN - Samsudin, Samsudin; Arif, Ahmad Yasin; Tjahyono, Ali Bowo (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
Before the emergence of formal educational institutions in the Islamic world, basic education institutions that live in the midst of society have developed, known as Kuttab. In Indonesia there are 17 Kuttab al-Fatih scattered in various cities and regencies. All of them have committed to strengthening their identity as a pillar of Islamic civilization by striving to restore the glory of Islam and the glory of knowledge. Kuttab al-Fatih Semarang is a representative Kuttab in developing Al-Quran-based Islamic education institutions through life skills education which is oriented towards personal skills and social skills. The results of the preliminary study show that there is strength in the implementation of life skills education through an emphasis on the internalization of values ​​on monotheism, morals, manners, courtesy and courtesy in society, manners and courtesy in the family, personality education, health, and morals. The approach used in this research is descriptive qualitative. Data collection techniques were carried out through documentation, observation, and interviews with teachers, guardians of students and students as samples of research objects.